THE STUDY OF FACTORS AFFECTING INTENTIONS TO USE CAR SHARING SERVICES IN THAILAND - Tayakee, Direk (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
This research is conducted to explore the factors affecting intentions to use car-sharing service in Thailand. There are six hypotheses and seven variables which are perceived quality, emotional value, consumer uncertainty, product image, consumer aspiration, attitude towards service, and intention to use. The primary data were gathered from 100 respondents who are living in Thailand and have experienced in carpooling service before at least one time. The questionnaires were distributed online through social networks. The five-point Likert scale was employed to measure the relationship among the determinants. Pearson Correlation Coefficient Analysis was applied as an instrument to estimate all hypotheses according to the research objectives. The finding of this study demonstrated that all hypotheses were supported, which showed the correlation among the variables used in this study.